Organización caótica en los Baupläne de Bilateria: simetría y complejidad animal - Rasskin-gutman, Diego (Coloquios de Paleontología, 2003)
The body plan of bilateral animals is characterized by the early specification of three embryonic axes. One of these axes defines the plane of bilateral symmetry of the future adult, ideally dividing these organisms in two mirror-image halves, left and right. Most species of this group exhibit significant and robust departures from this ideal bilateral plan, showing a suite of asymmetric characters. This paper characterizes different patterns and processes of asymmetry, highlighting both phylogenetic and ontogenetic aspects of such a basic feature of Bilateria. In addition, the role of symmetry and asymmetry as a way to increase the amount of complexity in animal organization is explored.